ANALISIS PENETAPAN DISPENSASI KAWIN DALAM PERSPEKTIF UNDANG-UNDANG PERLINDUNGAN ANAK (STUDI KASUS DI PENGADILAN AGAMA LIMBOTO TAHUN 2015-2016) - Sri Rahmawaty Yunus; Ahmad Faisal (Pascasarjana IAIN Sultan Amai Gorontalo, 2018)
This thesis described the establishment of judge in Limboto Religious Caurt in adjudicating marriage dispentation proposal. The proposal was requested by the parents for the children’s underage marriage, while in marriage law chapter 7 says that the marriage can be arranged at the age of 19 years old for men and 16yeras for women. Meanwhile, chilidren under 18 years old should have protection on thair rights and welfare as stated in Child Protection Law. Therefore, this research was conducted based on big concern on violation of chiledren’s rights. In this research, the researcher discussed problems on 1) how the judges considered the marriage dispentation proposal in Limboto Religious Caourt? And 2) how the judges determined the marriage dispensation proposal? This thesis was conducted through fielld research by means a research done in a particuler location ar area, and in this case it was located in Limboto Religious Court. This research used descriptive –analytic mathod where the problem of research was solved by describing and analytic it through data collection, composition, data analysis, data presentation and assessment on the reserch problem. The result showed that the implementation of marriage dispensation in Limboto Religious Court is relevant with legal substanceof child protection law as well as marriage law number 1 of 1974 in which it is based on principile of the law, it also prioritizes welfare of the chilidren who are mature enough ini building a new family. Those children in marriage dispensation have met standrs in child protection that puts forward the regulation’s best principle, the right to live, and appreciation for the children. Therefore, the marriage dispensation in Limboto Religious Caourt is not contradictory to the child protection law.